2010
DOI: 10.1007/s00432-010-0799-6
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer and adenomas are rare in individuals of Turkish descent living in the Zaanstreek region in the Netherlands

Abstract: BackgroundColorectal cancer is one of the most common malignancies in the Western world. Screening and detection of its precursor lesion, the adenoma could prevent development of colorectal cancer. Many studies have been done to evaluate the prevalence of colorectal cancer in different countries. In daily practice, it was noticed that colorectal cancer was rarely seen in patients of Turkish decent.AimTo evaluate the prevalence of colorectal cancer and adenoma in patients living in the Zaanstreek region, the Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…In an earlier study done in the Zaanstreek region it was already shown that colorectal cancer is rarely diagnosed in patients of Turkish descent. The present study confirms these earlier findings (7).…”
Section: Discussionsupporting
confidence: 94%
“…In an earlier study done in the Zaanstreek region it was already shown that colorectal cancer is rarely diagnosed in patients of Turkish descent. The present study confirms these earlier findings (7).…”
Section: Discussionsupporting
confidence: 94%
“…9,10 Adenomas are the main precursor lesions to most sporadic colorectal cancers and develop through the complex interactions of environmental and genetic risk factors. 11 Although recent reports have suggested that the risk of colorectal adenoma may be influenced by racial differences 12,13 in admixed populations, these findings are based on reported ethnicity rather than measured genetic ancestry. Self-reported measures of ethnicity in admixed populations are notoriously inaccurate regarding the individual ancestry.…”
Section: Introductionmentioning
confidence: 99%